CIM based earthquake risk management for resilience in smart cities - Korkmaz, Mustafa (Gebze Teknik Üniversitesi, Lisansüstü Eğitim Enstitüsü, 2025)
Urban resilience is a critical factor in mitigating the impacts of seismic hazards, particularly in regions with high earthquake risk. This study focuses on the development and implementation of a Seismic Risk Digital Twin (SRDT) integrated with City Information Management (CIM) for the Kocaeli region, an area known for its seismic vulnerability. The SRDT-CIM framework combines geospatial, structural, demographic, and dynamic data to create a comprehensive simulation model, enhancing seismic risk management, urban planning, and emergency response. The SRDT-CIM framework includes key components: a Hazard Model, an Exposure Model, a Vulnerability Model, a Response Model, and a Recovery Model, all supported by a robust CIM backbone. The Hazard Model employed a logictree approach with multiple ground motion prediction equations to assess seismic hazards and optimize predictive accuracy using on-site data. The Exposure Model analyzes building stock, categorized by function and construction era, integrating demographic distributions retrieved via APIs from address-based databases. The Vulnerability Model applies a hybrid approach, integrating standard vulnerability curves with structural analysis methods to assess potential damage and risk levels. CIM served as the core of the SRDT, enabling the seamless integration, storage, and management of diverse datasets, while ensuring interoperability and accessibility for stakeholders. This CIM-based approach facilitated dynamic updates, ensuring that real-time changes in urban and environmental parameters were reflected in the DT. The analysis identified critical challenges, including the need for improved planning of emergency muster sites and optimizing evacuation routes. The SRDT-CIM framework also emphasized the importance of real-time information on trapped individuals to enhance the efficiency of search and rescue operations. The SRDT-CIM also highlighted the importance of accurate, real-time information on trapped individuals for optimizing search and rescue operations. Comparative analysis demonstrated the advantages of the SRDT-CIM over traditional earthquake management techniques, particularly in predictive accuracy, resource allocation, and decision support capabilities. By integrating DT technology with CIM principles, this study underscores the transformative potential of innovative approaches in enhancing urban resilience, disaster preparedness, and cross-sector collaboration. The findings contribute to the growing body of knowledge on digital twins and City Information Management, offering a replicable framework for regions facing similar seismic risks.

Kentsel direnç, özellikle yüksek deprem riski taşıyan bölgelerde, sismik tehlikelerin etkilerini azaltmada kritik bir faktördür. Bu çalışma, sismik açıdan savunmasız bir bölge olan Kocaeli için Şehir Bilgi Yönetimi (CIM) ile entegre edilmiş bir Sismik Risk Dijital İkizi'nin (SRDT) geliştirilmesine ve uygulanmasına odaklanmaktadır. SRDT-CIM çerçevesi, jeo-uzamsal, yapısal, demografik ve dinamik verileri bir araya getirerek kapsamlı bir simülasyon modeli oluşturmakta ve böylece sismik risk yönetimi, kentsel planlama ve acil durum müdahale süreçlerini geliştirmektedir. SRDT-CIM çerçevesi, bir Tehlike Modeli, Maruziyet Modeli, Zarar Görebilirlik Modeli, Müdahale Modeli ve İyileşme Modeli olmak üzere temel bileşenleri içermektedir; bu bileşenlerin tümü güçlü bir CIM altyapısıyla desteklenmiştir. Tehlike Modeli, sismik tehlikeleri değerlendirmek ve saha verileriyle tahmin doğruluğunu optimize etmek için çoklu yer hareketi tahmin denklemleri içeren bir mantık ağacı yaklaşımı kullanmıştır. Maruziyet Modeli, bina stokunu işlevi ve yapım dönemi temelinde kategorize ederek analiz etmiş ve adres tabanlı veri tabanlarından API'ler aracılığıyla demografik dağılımları entegre etmiştir. Zarar Görebilirlik Modeli, standart zarar görebilirlik eğrilerini yapısal analiz yöntemleriyle birleştiren hibrit bir yaklaşım uygulayarak olası hasar ve risk seviyelerini değerlendirmiştir. CIM, SRDT'nin çekirdeği olarak, çeşitli veri kümelerinin sorunsuz bir şekilde entegrasyonunu, saklanmasını ve yönetimini sağlayarak paydaşlar için erişilebilirlik ve birlikte çalışabilirlik sağlamıştır. Bu CIM tabanlı yaklaşım, kentsel ve çevresel parametrelerdeki gerçek zamanlı değişikliklerin dijital ikize yansıtılmasını kolaylaştırmıştır. Analiz, acil durum toplanma alanlarının iyileştirilmiş planlanması ve tahliye yollarının optimize edilmesi ihtiyacını içeren kritik zorlukları ortaya koymuştur. SRDT-CIM çerçevesi, aynı zamanda enkaz altında mahsur kalan bireyler hakkında gerçek zamanlı bilginin arama ve kurtarma operasyonlarının etkinliğini artırmadaki önemini vurgulamıştır. Karşılaştırmalı analiz, SRDT-CIM'in özellikle tahmin doğruluğu, kaynak tahsisi ve karar destek yetenekleri açısından geleneksel deprem yönetimi tekniklerine göre avantajlarını göstermiştir. Bu çalışma, dijital ikiz teknolojisinin CIM ilkeleriyle entegrasyonunun, kentsel direnç, afet hazırlığı ve sektörler arası iş birliğini geliştirmedeki dönüştürücü potansiyelini vurgulamaktadır. Bulgular, dijital ikizler ve Şehir Bilgi Yönetimi konusundaki bilgi birikimine katkıda bulunarak benzer sismik risklerle karşı karşıya kalan bölgeler için tekrarlanabilir bir çerçeve sunmaktadır.
Akıllı şehirlerde dirençlilik için CIM tabanlı deprem risk yönetimi
Keywords: Deprem Mühendisliği; Earthquake Engineering; İnşaat Mühendisliği